nn - Losoncz, Mark (Glasnik Advokatske komore Vojvodine, 2020)
The article focuses on the concept of the state of exception by taking into consideration both its juridical and political meanings. By criticizing Agamben's analysis of the state of exception, the article offers an alternative genses of the state of exception, with special attention to the role of liberalism, the nuclear war and the state of exception that was implemented after the terrorist attacks of 9/11. On the other hand, the article emphasizes that one should not describe the state of exception as an "anomic state"  that suspends law, on the contrary, within the complex social relations of the state of exception, the lawful and the un-lawful are often "organically" entwined. At the end, the article focuses on the neoliberal relation to the state of exception.
Keywords: state of exception, illegality and anomy, Agamben, liberalism, nuclear war, neoliberalism